Balancing Language Skills in Arabic Assessment: Challenges of Curriculum Implementation in an Islamic Integrated School - Adibah Ulaya Putri; Maman Abdurrahman; Mad ‘Ali (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
This study examines Arabic language assessment practices within curriculum implementation at an Islamic Integrated Junior High School (SMPIT), employing a qualitative instrumental case study design with teacher as participant. Data were collected through semi-structured interviews and document analysis, then analyzed using inductive thematic analysis. The findings reveal that, within this specific institutional context, assessment practices are predominantly structured around written tests that emphasize vocabulary (mufradat), grammar (qawa'id), and translation activities, a pattern driven primarily by the school's curriculum requirements rather than the teacher's individual choices. Assessment of the four language skills is imbalanced: speaking is partially addressed through dialogue and video projects, while listening, reading, and writing receive limited attention in the formal assessment system. Digital platforms such as Google Forms and Quizizz have been integrated into assessment, though their alignment with pedagogical goals requires further development. Key challenges include low student motivation, limited hijaiyyah literacy, and demanding curriculum targets. The study concludes that Arabic language assessment practices in this context are shaped more by institutional curriculum structures rather than by individual teacher agency.